PENGARUH MEKANISME INTERNAL CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks LQ-45 di Bursa Efek Indonesia tahun 2017-2021) - Jennifer Claverine Pratama; Abdul Rohman (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of the characteristics of the internal corporate governance mechanisms such as audit committee size, audit committee expertise, number of audit committee meetings, board of commissioner’s size, and number of board of commissioners meeting on audit report lag in companies listed on the LQ-45 index. The sample used in this research is a company listed on the LQ-45 index on the Indonesia stock exchange for 2017-2021 with a total sample of 125 samples. The sample selection was based on the use of purposive sampling method with criteria and conditions determined by the researcher. The analytical method used in this research is multiple linear regression analysis method. The results of this study found that audit committee expertise has a positive and significant effect on audit report lag. Meanwhile, the size of the board of commissioners and the number of board of commissioners meeting have a negative and significant effect on audit report lag. However, it was found that the size of the audit committee and the number of audit committee meetings had a negative but not have a significant effect to audit report lag.